NENSEK DAN RUANG PEREMPUAN SASAK DI DUSUN KELOKE DESA BATUJAI KACAMATAN PRAYA BARAT KABUPATEN LOMBOK TENGAH - Liza Hani Saroya Wardi; Rini S. Saptaningtiyas; Zaedar Gazalba; Pascaghana Jayatri Putra; Muhammad Iqbal Raissilki (Bajang Institute, 2024)
This research aims to explain what and how weaving (menenun) and women's spaces exist, develop and survive, are lived, addressed in relation to the environment in Keloke Hamlet. Data was obtained through field observations and interviews. The findings obtained are that weaving is a legacy of Keloke women's ancestors which is a tradition of Keloke women which is used as their attitude to life and identity. The findings obtained are that weaving is a legacy of Keloke women's ancestors which is a tradition of Keloke women which is used as their attitude to life and identity. The practice of weaving is guided by existing cultural values and gives certain meaning to their lives. The existence of this weaving presents a women's space in which Keloke women carry out weaving activities and experience weaving attitudes that strengthen their identity as inheritors of the culture left by their ancestors.